2018
DOI: 10.1002/ijgo.12705
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare provider interaction and other predictors of long‐acting reversible contraception adoption among women in Nigeria

Abstract: Objective To test the association between healthcare provider communication and adoption of long‐acting reversible contraception (LARC) among women in Nigeria. Methods The present cross‐sectional observational secondary analysis included women aged 18–49 who were interviewed between June 1 and July 31, 2014, at selected family planning sites in Ibadan and Kaduna, Nigeria. A multivariate generalized estimating equation was utilized to assess the predictors of LARC adoption. Results 597 women were interviewed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…CTG training and mentoring addressed this issue. In response to this and a growing body of literature on the effect of contraceptive counseling on uptake of post abortion contraception ( 11 , 33 , 36 , 37 ), CTG trained providers to use a time allocation strategy for contraceptive counseling, whereby 70% of counseling time is spent on LARCs, and 30% is spent on short acting methods ( 38 ). Alongside ongoing provider mentorship, implementation of this timing strategy enabled providers to grow their capacity and confidence to administer LARC services.…”
Section: Discussionmentioning
confidence: 99%
“…CTG training and mentoring addressed this issue. In response to this and a growing body of literature on the effect of contraceptive counseling on uptake of post abortion contraception ( 11 , 33 , 36 , 37 ), CTG trained providers to use a time allocation strategy for contraceptive counseling, whereby 70% of counseling time is spent on LARCs, and 30% is spent on short acting methods ( 38 ). Alongside ongoing provider mentorship, implementation of this timing strategy enabled providers to grow their capacity and confidence to administer LARC services.…”
Section: Discussionmentioning
confidence: 99%
“…Providers also brought up concerns about inadequate supplies. While family planning nurse supply concerns revolved around opportunities to enhance engagement with clients, particularly with follow-up, which has been noted as an essential aspect of quality of care (11,14,24,25) -CHWs concerns mostly centered on logistical needs, a concern also linked to impacts on quality of care (6,8,23). Notably, among CHWS, these concerns were brought up much more often in Nyamasheke as compared to Musanze.…”
Section: Discussionmentioning
confidence: 99%
“…Building relationships with clients based around both empowerment and empathy, providers share how they listen to and work collaboratively with them to nd solutions to their problems, an important aspect of quality of care (14). Research has shown that when providers treat clients humanely, and develop a relationship with them, clients are more likely to seek out health providers in the future (28), initiating and continuing contraceptive use (7,(29)(30)(31)(32)(33)(34), as well as selecting longer term methods contraceptive use (24). Providers, and clients, both noted the importance of reliable access to providers and methods.…”
Section: Discussionmentioning
confidence: 99%
“…Karenanya kami merekomendasikan perlunya konsultasi pilihan kontraepsi sebelum memilih dan menggunakan kontrasepsi yang bertujuan untuk pertimbangan penggunaan kontrasepsi sesuai kebutuhan akseptor. Hal ini berdasar pada penelitian sebelumnya dimana peningkatan komunikasi pasien dan penyedia layanan kesehatan yang melibatkan informasi tentang semua metode kontrasepsi, dan tindak lanjut yang direncanakan dapat memainkan peran sentral dalam meningkatkan permintaan, dan penggunaan kontrasepsi long-acting reversible contraceptive (LARC) (Kalra, et al, 2018).…”
Section: Pembahasanunclassified